Mature iPSC-derived astrocytes of an ALS/FTD patient carrying the TDP43A90V mutation display a mild reactive state and release polyP toxic to motoneurons - Rojas, Fabiola; Aguilar, Rodrigo; Almeida, Sandra; Fritz, Elsa; Corvalán, Daniela; Ampuero, Estibaliz; Abarzúa, Sebastián; Garcés, Polett; Amaro, Armando; Diaz, Iván; Arredondo, Cristian; Cortes, Nicole; et al. (Frontiers in Cell and Developmental Biology, 2023)
Astrocytes play a critical role in the maintenance of a healthy central nervous system and astrocyte dysfunction has been implicated in various neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). There is compelling evidence that mouse and human ALS and ALS/FTD astrocytes can reduce the number of healthy wild-type motoneurons (MNs) in co-cultures or after treatment with astrocyte conditioned media (ACM), independently of their genotype. A growing number of studies have shown that soluble toxic factor(s) in the ACM cause non-cell autonomous MN death, including our recent identification of inorganic polyphosphate (polyP) that is excessively released from mouse primary astrocytes (SOD1, TARDBP, and C9ORF72) and human induced pluripotent stem cells (iPSC)-derived astrocytes (TARDBP) to kill MNs. However, others have reported that astrocytes carrying mutant TDP43 do not produce detectable MN toxicity. This controversy is likely to arise from the findings that human iPSC-derived astrocytes exhibit a rather immature and/or reactive phenotype in a number of studies. Here, we have succeeded in generating a highly homogenous population of functional quiescent mature astrocytes from control subject iPSCs. Using identical conditions, we also generated mature astrocytes from an ALS/FTD patient carrying the TDP43A90V mutation. These mutant TDP43 patient-derived astrocytes exhibit key pathological hallmarks, including enhanced cytoplasmic TDP-43 and polyP levels. Additionally, mutant TDP43 astrocytes displayed a mild reactive signature and an aberrant function as they were unable to promote synaptogenesis of hippocampal neurons. The polyP-dependent neurotoxic nature of the TDP43A90V mutation was further confirmed as neutralization of polyP in ACM derived from mutant TDP43 astrocytes prevented MN death. Our results establish that human astrocytes carrying the TDP43A90V mutation exhibit a cell-autonomous pathological signature, hence providing an experimental model to decipher the molecular mechanisms underlying the generation of the neurotoxic phenotype.